New species of Platypalpus (Diptera: Hybotidae) from the Democratic Republic of the Congo - Grootaert, Patrick; Shamshev, Igor (European Journal of Taxonomy, 2014)
Six new species of Platypalpus Macquart, 1827 are described from tropical forest at Yangambi (Democratic Republic of the Congo): Platypalpus bolikoi sp. nov., P. ikoso sp. nov., P. lokonda sp. nov., P. manjano sp. nov., P. saffradi sp. nov. and P. yangambensis sp. nov. All species are photographed and, except for P. saffradi sp. nov. known only from females, male terminalia are illustrated for all. A key is provided for the six species of DR Congo. COI barcodes are available for all species at GenBank.